Reconstruction of Miocene vegetation based on the palynology of core material from Langebaanweg, South Africa - Moseri, Moteng Elizabeth (My University, 2022)
The Cape Floristic Region (CFR) houses a diverse range of plant species that are characteristic of a Mediterranean-type climate that was established in the Neogene. The Elandsfontyn Formation at Langebaanweg( LBW) revealsthe evolutionary history of fynbos vegetation, the exact timing of which is still uncertain. Pollen, spores and dinoflagellate cysts recovered from Core BH2 preserving ElandsfontynFormation deposits are identified to conduct a palaeoenvironmental reconstruction of the deposits at LBW. A standard palynological procedure was applied to process the sediments and produce 76 samples which were analysed with a light microscope. A total of 104 palynomorphtaxa including pollen, spores and dinoflagellate cysts were recorded to determine the timing of evolution of the fynbos biome and statistically analysed to create clusters of palynomorph indicators, which may be linked to certain climatic parameters. The palynological and statistical results confirm the existence of a subtropical-tropical forest dominated by Podocarpaceae, palms, vines and ferns, providing evidence of wet conditions caused by summer rainfall. The possible existence of Araucariaceae – a typical Gondwana element currently extinct in Africa - is documented in this study but requires confirmation from SEM studies. Wetlands comprising Sparganiaceae, Restionaceae, Cyperaceae and Poaceae were common, pointing to a high water table. Mangrove tree pollen were rarely recorded, possibly implying that mangrove swamps might have been confined to the coastline. Patches of proto-fynbos probably provided an understorey component of the subtropical forests and co-fluctuated with the forest elements. A considerable marine influence was imposed on the terrestrial environment, inferred by three marine transgressions in the Apteodinium spiridoideszone (18.96–18.24 m) and a fourth and final event i n the Operculodinium centrocarpumzone (16.865–13.4 m), which are probably linked to global late Oligocene sealevel changes. Dinoflagellate cysts belonging to Apteodinium spiridoides, Opeculodinium centrocarpum, Spiniferites mirabilis were abundant and occurred with other marine indicators,such as benthic microforaminiferal test linings and algal cysts. Savanna woodlands with Alchornea (Psilatricolporites quenua), Combretaceae and Brachystegia (Peregrinipollis nigericus) gradually replaced the subtropical forests, possibly due to more arid conditions and enhanced seasonality. Similar assemblages with common extinct taxa were recorded at Saldanha Bay, Rondeberg, Noordhoek, and Knysna and show possible floristic links to sites in other Southern Hemisphere regions, including South America, Antarctica, Australia and New Zealand. A late Oligocene (early Chattian) to early Miocene (early Burdigalian) age is inferred for Elandsfontyn Formation at LBWbased on the presence of Mutisiapollis viteauensis, Tubuliflodites antipodica, Apteodinium spiridoides, Chiropteridium lobospinosum and Cordosphaeridium minimum.
A dissertation submitted to the School of Geosciences, Faculty of Science, University of theWitwatersrand, in fulfilment of the requirements for the degree of Master of Science, 2022